Psicoterapia online, un’esperienza nuova - Emiliozzi, Andrea; Lucarini, Emanuela; Sneider, Giovanni; Sneider, Maria; Trevisan, Niccolò (Il sogno della farfalla, 2021)
At the beginning of March 2020, the serious danger represented by the Covid-19 deadly disease had become a certainty therefore leading to the interruption of the in presence psychotherapy. In those days, among many psychotherapists trained in the context of the Analisi Collettiva, arose the need to establish a group in order to discuss a possible alternative to the traditional setting. This article stems out of the debate and clinical practice consequently experienced. During the therapeutic practice it has been observed how facial mimicry, voice’s sound and oniric images told by the patients, still allowed to establish a non-conscious relation, consequently leading to the decision to carry on the therapeutic treatment even in the context of a distance setting.